2015
DOI: 10.1158/0008-5472.can-14-2304
|View full text |Cite
|
Sign up to set email alerts
|

miR30a Inhibits LOX Expression and Anaplastic Thyroid Cancer Progression

Abstract: Anaplastic thyroid cancer (ATC) is one of the most lethal human malignancies, but its genetic drivers remain little understood. In this study, we report losses in expression of the miRNA miR30a, which is downregulated in ATC compared with differentiated thyroid cancer and normal tissue. miR30a downregulation was associated with advanced differentiated thyroid cancer and higher mortality. Mechanistically, we found miR30a decreased cellular invasion and migration, epithelialmesenchymal transition marker levels, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 33 publications
2
69
0
1
Order By: Relevance
“…Another study on the possible use of miRs in therapies of ATC focused on mir-30a, which turned out to be a direct negative regulator of lysis oxidase (LOX). Restored expression of miR-30a in a mouse model resulted in smaller metastases but did not affect the tumor growth (81). The role of the miR-30 family in the pathogenesis of ATC was additionally supported in a study by Hebrant et al (82), which also identified miR-29a as the second regulator of the LOX gene.…”
Section: The Potential Of Micrornas In Thyroid Cancer Treatmentmentioning
confidence: 82%
“…Another study on the possible use of miRs in therapies of ATC focused on mir-30a, which turned out to be a direct negative regulator of lysis oxidase (LOX). Restored expression of miR-30a in a mouse model resulted in smaller metastases but did not affect the tumor growth (81). The role of the miR-30 family in the pathogenesis of ATC was additionally supported in a study by Hebrant et al (82), which also identified miR-29a as the second regulator of the LOX gene.…”
Section: The Potential Of Micrornas In Thyroid Cancer Treatmentmentioning
confidence: 82%
“…These genes include PIK3CD [3], VIM [10], SEPT7 [12], DLL4 [9], CD99 [8], LOX [7], DTL [4], IRS2 [5], FOXL2 [13], etc. In addition, the signaling pathways of miR-30a implicated in the pathogenesis of cancers have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear now that miRNAs perform their biological functions by guiding the RNA-induced silencing complex (RISC) toward 3′ UTR of target mRNAs [2]. miR-30a locates in human chromosome 6q13 and increasing evidence indicates that miR-30a can act as a tumor suppressor to inhibit the growth of various tumors including colorectal carcinoma [3][4][5], breast cancer [6], anaplastic thyroid cancer [7], Ewing's tumor [8], clear cell renal cell carcinoma [9], gastric cancer [10], and nasopharyngeal carcinoma [10,11]. In addition, miR-30a also shows the feature of an oncogene.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of miR-30a were found to remarkably descend in most of cancer tissues compared with those in adjacent non-tumorous tissues, such as colorectal cancer [67, 68], hepatocellular carcinoma [69, 70], breast cancer [71], renal cell carcinoma [72], chondrosarcoma [73], ovarian papillary serous carcinoma [74], and anaplastic thyroid cancer [75]. Furthermore, miR-30a expression decreased in patients with shorter overall survival and disease-free survival time in patients with NSCLC [19] and urothelial carcinoma of bladder [76], consistent with the lower expression of miR-30a in tumor tissues compared to their non-tumor lung tissues.…”
Section: Expression and The Clinical Significance Of Mir-30a In Cancermentioning
confidence: 99%
“…Furthermore, Insulin-like growth factor I (IGF-I) could induce EMT of NPC through IGF-IR-Src-miR-30a-E-cadherin pathway [107]. MiR-30a played a critical functional role in inhibiting LOX expression and thyroid cancer progression, including cell proliferation, invasion, and migration [75]. By targeting osteogenesis transcription factor runt-related transcription factor 2 (RUNX2), miR-30a stimulated adipogenesis during the development of adipocyte [108], influenced the osteoclast differentiation and osteolysis formation [109], and inhibited apoptosis [110] in giant cell tumor of bone.…”
Section: Activities Of Mir-30a In Cancer Progressionmentioning
confidence: 99%